"It gives her a sense of accomplishment": What parents say when children with disabilities ride - Buchanan, Alice M; Higgins, A (European Journal of Adapted Physical Activity, 2023)
This interpretive study explored participants' perceptions of their child's involvement in Equine-Assisted Activities and Therapies (EAAT). EAAT is implemented with a horse and is based on the notion that interacting with the horse has positive benefits. Such activity is nearly always reported to have positive effects on the child. Few studies have investigated the perceptions of the parents of their children's participation in horseback riding activities. The purpose of this study is to determine how parents and/or guardians perceive how EAAT impacts their young riders, and the epiphanic ways in which the parents view those changes. Seven parents of participating children were purposefully sampled. Riders included five girls (5-10 years old) and six boys (6-16 years old) with cognitive and/or emotional disabilities including Post-Traumatic Stress Disorder (PTSD), Autism Spectrum Disorder, Down syndrome, and more. Findings were analyzed through an interpretive lens of epiphany. Participants spoke of the positive ways in which they and their children were accepted, and discussed improvements in children's strength, social development, and specific individual needs. Parents' views of the impact on their children are essential to improving service and advocacy for their children.
Keywords: Parents; sport pro děti a mládež; Children with Disabilities; Social Perception; Humans; dětská psychologie; Equine-Assisted Therapy; Youth Sports; Patient Satisfaction; Sports for Persons with Disabilities; Sentiment Analysis; sociální percepce; sporty pro handicapované; terapie využívající koní; postižené děti; výsledek terapie; rodiče; Treatment Outcome; spokojenost pacientů; lidé; postojová analýza; Psychology, Child